She stooped to conquer space - Abd Razak, Dzulkifli (2008)
EACH year, on Dec 10, scientists will be anxiously waiting for the Nobel Prize ceremony in Stockholm. It is after all deemed as science's most prestigious annual event. For Malaysia, the date this year took a different significance with the departure of one of the nation's renowned scientists, the head of Angkasa, the National Space Agency. Professor Datuk Dr Mazlan Othman is reported to have left the country to once again take up appointment as head and director of the United Nations Office for Outer Space Affairs based in Vienna.